Factors influencing secondary school students' nutrition, mindfulness, and academic performance in Nan Province, Thailand. - Ei Zar Lwin; Dorn Watthanakulpanich; Athit Phetrak; Ngamphol Soonthornworasiri; Pattaneeya Prangthip (PLoS ONE)
Academic performance is crucial for future educational endeavors of students. However, there has been a concerning decline over time. This study aimed to investigate the association between nutritional status, environmental factors, mindfulness, and academic performance among students at Bo Kluea School in Nan province, Thailand. A cross-sectional study was conducted involving 350 students in grades 8-11 using questionnaires, measurements, and academic records. Results showed that female students performed significantly better academically compared to males(71.9% vs 56.4% achieving good grades; compared to p < 0.001, OR = 3.583, 95%CI = 1.663-7.719). Age, junk food consumption, BMI, and mindfulness were identified as factors influencing academic performance. Students aged 16-18 years were 2.224 times more likely to achieve good academic performance compared to younger students (p = 0.015, OR = 2.224, 95%CI = 1.164-4.247). Significant associations were found between gender, age, waist circumference, mindfulness, and nutritional status. Female students and those with normal waist circumference or good mindfulness were more likely to have a normal BMI (p = 0.019, OR = 1.794, 95%CI = 1.101-2.922). Positive attitudes towards nutrition were associated with better academic performance (60.1% achieving good grades;p = 0.044, AOR = 1.543, 95%CI = 1.010-2.356). This study highlights the interconnectedness of these factors and their importance in in improving academic results. Further research is need to confirm these findings and overcome study limitations.